Pengaruh Pengampunan Pajak dan Kemudahan Administrasi Pajak Terhadap Kepatuhan Wajib Pajak Orang Pribadi pada KPP Pratama Jakarta Penjaringan - Rudi Kristanto; M. Anjar Nurul Hayat (Institut Ilmu Sosial dan Manajemen STIAMI, 2018)
The purpose of this study is to determine the implementation of tax pardons conducted by KPP Pratama Jakarta Penjaringan, ease of tax administration and changes in taxpayer compliance increase. The conclusion of research, that the implementation of tax amnesty and the ease of tax administration conducted by KPP Penjaringan in the period 2015-2017 have a strong influence on taxpayer compliance. The coefficient of determination (adjusted R2) shows the variable of Tax Amnesty (X1) and Ease of Tax Administration (X2) can explain or explain Personal Taxpayer Compliance KPP Pratama Jakarta Penjaringan (Y) of 28%. KPP is advised to improve tax administration system, service to Taxpayer, tax law enforcement and tax rate and intensive socialization to taxpayer about good tax administration knowledge.